2009
DOI: 10.1021/np900158f
|View full text |Cite
|
Sign up to set email alerts
|

Influenza A (H1N1) Antiviral and Cytotoxic Agents from Ferula assa-foetida

Abstract: Two new sesquiterpene coumarins, designated 5'-acetoxy-8'-hydroxyumbelliprenin (1) and 10'R-acetoxy-11'-hydroxyumbelliprenin (2), and a new diterpene, 15-hydroxy-6-en-dehydroabietic acid (3), along with 27 known compounds, were isolated from a CHCl(3)-soluble extract of Ferula assa-foetida through bioassay-guided fractionation. The structures of the new metabolites 1-3 were identified by spectroscopic data interpretation and by the Mosher ester method. Compounds 4 and 6-13 showed greater potency against influe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
85
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(90 citation statements)
references
References 32 publications
4
85
0
1
Order By: Relevance
“…The mentioned study further streamlined for use of this gum resin in the upper respiratory diseases in traditional medicine. [7] Antifungal Activity The oils extracted from all seeds except mustard showed a variation of the degree of fungicidal activity against experimental species. Asafoetida oil considerably inhibited the growth of all test fungi except.…”
Section: Antiviral Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…The mentioned study further streamlined for use of this gum resin in the upper respiratory diseases in traditional medicine. [7] Antifungal Activity The oils extracted from all seeds except mustard showed a variation of the degree of fungicidal activity against experimental species. Asafoetida oil considerably inhibited the growth of all test fungi except.…”
Section: Antiviral Activitymentioning
confidence: 99%
“…c. 10-R-acetoxy-11 hydroxyumbelliprenin has antiviral (influenza H1N1) activity. [7] d. Epi-conferdione has antiviral (influenza H1N1). [7] e. Conferol has antiviral (influenza H1N1), cytotoxic (HepG2, Hep3B, and MCF-7), synergistic effect with anticancer agents (vincristine).…”
Section: Biological Activities Reported From the Bioactive Coumarins mentioning
confidence: 99%
See 2 more Smart Citations
“…Traditionally, it is used for the treatment of different diseases, such as stomach ache, asthma, epilepsy, flatulence, weak digestion, intestinal parasites and influenza [12]. Recent pharmacological and biological studies have also shown several activities, such as antioxidant [13], antiviral [14], antimicrobial [15], antispasmodic and hypotensive [16], and antidiabetic [5,17].…”
Section: Introductionmentioning
confidence: 99%